Soil pollution : from monitoring to remediation - Duarte, Armando C.; Cachada, Anabela; Rocha-Santos, Teresa (London, United Kingdom : Academic Press, an imprint of Elsevier, 2018)
This book provides comprehensive information on soil pollution, including causes, distribution, transport, the transformation and fate of pollutants in soil, and metabolite accumulation. It covers organic, inorganic and nanoparticle pollutants and methodologies for their monitoring, and features a critical discussion on ecotoxicological and human effects of soil pollution, and strategies for soil protection and remediation.
1. Soil and pollution : an introduction to the main issues / Anabela Cachada, Teresa Rocha-Santos and Armando C. Duarte -- 2. Distribution, transport and fate of pollutants / Nuno Duraes [and three others] -- 3. Changes in soil ecosystem structure and functions due to soil contamination / Rui G. Morgado, Susana Loureiro and Maria N. Gonzalez-Alcaraz -- 4. Pollutants transformation and metabolite accumulation in soils / Naser A. Anjum [and five others] -- 5. Organic pollutants in soils / Regina M.B.O. Duarte, Joao T.V. Matos and Nicola Senesi -- 6. Inorganic pollutants in soils / Carla Patinha [and three others] -- 7. Nanomaterials as soil pollutants / Susana Loureiro [and eight others] -- 8. Ecotoxicological effects and risk assessment of pollutants / Ruth Pereira [and five others] -- 9. Human health risks and soil pollution / Sonia M. Rodrigues and Paul F.A.M. Romkens -- 10. Strategies for soil protection and remediation / David Fangueiro [and four others].
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed October 10, 2017).
Includes bibliographical references and index.
Keywords: Soil pollution; Sols -- Pollution; soil pollution; TECHNOLOGY & ENGINEERING -- Environmental -- General; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- Soil Science; Soil pollution